Female Transformational Leadership and its Influence on Psychosocial Risks in Pharmacies in the Historic Center of Puebla. - Gutiérrez Herrera, Itzel Guadalupe (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2024)
OBJECTIVE: To identify the psychosocial risks that most influence the staff in the sales area of ​​the pharmacies of the Historic Center of Puebla.MATERIAL AND METHOD: A population census was carried out in the 84 pharmacies of the Historic Center of Puebla and for each study unit, the reference guide III of NOM 035 was applied to a non-probabilistic sample of two sales study subjects. The data were examined with the SPSS statistical package, obtaining an internal reliability consistency of 0.859 Cronbach's Alpha and regarding the analysis, it was a descriptive and inferential statistics.RESULTS: The results indicated a high level of psychosocial risk, which are: the workday with 44.64% and the insufficient sense of belonging and job instability with 100%.CONCLUSIONS: The psychosocial risk domains with the greatest influence on transformational leadership were: the workday with 25% and the insufficient sense of belonging and job instability with 45%, since the greater the presence of transformational leadership, the respect for the workday improves. work and the greater the presence of transformational leadership, there is a greater sense of belonging and job stability.
Keywords: Psychosocial risk; Transformational leadership; Pharmacies.